Developing an emergency nursing short course in Tanzania - Cunningham, C.; Brysiewicz, P.; Sepeku, A.; White, L.; Murray, B.; Lobue, N.; Sawe, H. (African Journal of Emergency Medicine, 2017)
Abstract Nurses are the largest group of healthcare workers in Africa. By adequately equipping nurses to identify, intervene and care for emergency conditions, emergency healthcare systems can be strengthened. To address this need, a nursing working group was formed within the African Federation for Emergency Medicine (AFEM). The aim of this international emergency nursing group was to develop a guiding document to help improve emergency nursing skills within Africa. Using this guiding document, a group of Tanzanian clinical nurse trainers was selected to develop a context specific short course. They used this guiding document as a foundation to improve skill development. The pilot course was well received and has since expanded to training in five regions within the United Republic of Tanzania. The clinical nurse trainers leading the course, are supported by a mentorship programme with competent educators within a global emergency nursing infrastructure. This course, a combination of local knowledge, formal mentorship programs, and international nursing support, demonstrates that investing in the improvement of emergency nursing skills can have high impact results with low-cost. This will ultimately improve emergency care on the continent.
Keywords: -FullBiblioUHMLgen; -RRQ:H:final; -RRQ:U:final; A:Africa; C:Tanzania; CA:AandC; CL:en; CLL:en; CLS:en; CT:A; CT:C; CT:F; CT:P; CT:R; CT:T; F:Improvement; P:health; P:media; P:nurse; R:impact; T:Training; T:trainee; publicImportV1